2012
DOI: 10.1007/s12262-011-0402-7
|View full text |Cite
|
Sign up to set email alerts
|

Revisional Surgery after Heller Myotomy for Treatment of Achalasia: A Comparative Analysis Focusing on Operative Approach

Abstract: Surgical myotomy is the gold standard in therapy for achalasia, but treatment failures occur and require revisional surgery. A MEDLINE search of peer-reviewed articles published in English from 1970 to December 2008 was performed using the following terms: esophageal achalasia, Heller myotomy, and revisional surgery. Thirty-three articles satisfied our inclusion criteria. A total of 12,727 patients, with mean age of 43.3 years (males 46% and females 50%), underwent Heller myotomy (open 94.8% and laparoscopic 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…6 Carter JD et al had slightly more male patients as compared to female with average age incidence of 49 years. 7 Zaninotto G et al had slightly higher female incidence than male with mean age of presentation was 41 years.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…6 Carter JD et al had slightly more male patients as compared to female with average age incidence of 49 years. 7 Zaninotto G et al had slightly higher female incidence than male with mean age of presentation was 41 years.…”
Section: Discussionmentioning
confidence: 94%
“…In most of the studies no mortalities were found except for Gouda BP at all had 0.63% mortality due to splenic capsule tear and severe sepsis. 6 In present study on laparoscopic Heller's cardiomyotomy for achalasia cardia, all patients were undergone laparoscopic repair and no conversion to open procedure. On an average mean hospital stay was 4.6 days (3 days-10 days) which was much less compared to open (thoracotomy or laparotomy) or thoracoscopic procedure.…”
mentioning
confidence: 91%
“…Severe reflux after myotomy was identified as a cause of revision surgery in 32% of patients in the study by Gouda et al . [ 26 ] Dysphagia due to peptic oesophagitis or stricture is easily assessed by flexible endoscope; in doubtful cases, it may be useful for manometry and 24-h oesophageal pH-metry.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Squamous cell carcinoma was the indication of 3.04% of revision surgeries in the series of Gouda et al . [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…A challenging scenario arises in patients who have undergone a LHM that either fails to control their symptoms adequately or symptoms recur after initial success. The most common cause of treatment failure or recurrent symptoms after LHM is an incomplete myotomy, 69 and more specifically, with failure to extend the myotomy at least 2-3 cm distal to the GE junction. 56,[70][71][72] Other less common causes include a tight or disrupted fundoplication, severe reflux, or severe fibrosis.…”
Section: Heller Myotomymentioning
confidence: 99%